Leaving no one behind: the impact of disability and socioeconomic status on maternal continuum of care - Ebisa Turi; Lisa Gold; Ha N.D Le; Hasheem Mannan; Eric H.Y. Lau; Julie Abimanyi-Ochom (BMC Public Health)
Abstract Background To ensure that women with disabilities (WwD) have access to essential maternal health services, understanding their service utilization within the continuum of care (CoC) framework is vital. However, the influence of women’s disability status on maternal CoC has not been fully explored. Hence, this paper examines the completion level and inequality of basic maternal CoC, as well as its association with women’s disability status. Methods We conducted analyses on demographic and health survey data of nine low- and middle-income countries collected between 2016 and 2022. Disability among reproductive-age women was assessed using the Washington Group Short Set questionnaires. The maternal CoC was defined to include receiving four or more antenatal visits, skilled birth attendance and obtaining timely postnatal care. Concentration indices were used to measure wealth-related inequalities in completing CoC. Multivariable logistic regression was used to identify factors associated with inequalities in the CoC completion. Results A total of 14.0% of women had a disability of at least some difficulty in one domain of function. Among women who made their first antenatal care contact, only 35.8% completed CoC; this percentage was lower among women with disability (32.7%). The odds of completing CoC was lower among WwD (AOR = 0.89, 95% CI: 0.83–0.95). Higher maternal education (AOR = 1.63–2.27), female-headed household (AOR = 1.14, 95% CI: 1.07–1.22), currently working (AOR = 1.29, 95% CI:1.22–1.37) and wealth quintile (increasing from poor to the richest (AOR = 1.24–2.18) were positively associated with higher odds of completing the CoC. We found overall pro-rich inequality in CoC completion (CI 0.27: 95%CI: 0.26–0.29). Higher inequalities were observed in countries with lower coverage of maternal healthcare services. Conclusion Maternal CoC completion was lower among WwD, especially those with lower socioeconomic status. Effective strategies that ensure disability-friendly maternal health care services will play a pivotal role. Maternal health service programs should prioritize women’s disability status alongside other key socioeconomic factors and address health care barriers to ensure more equitable and comprehensive maternal health care.